Pengaruh Profitabilitas, Ukuran Perusahaan dan Likuiditas terhadap Harga Saham - Fadhila Annisa Pranandyasari; Munari Munari (Ekonomis: Journal of Economics and Business, 2023)
The purpose of this study is to investigate how profitability, firm size, and liquidity affect stock prices. This study uses infrastructure companies that will be listed on the Indonesia Stock Exchange in 2021 as the population. Purposive sampling is the method of sampling that is used. A method of sampling called "purposeful sampling" is one that the researcher chooses based on a set of criteria.33 businesses were included in the sample, which was selected using predetermined criteria. The Indonesia Stock Exchange's annual financial reports are used as secondary data in this investigation. The multiple linear regression technique was used to analyze the data. According to the findings of this study, the share prices of infrastructure sector companies that will be listed on the IDX in 2021 have no effect on profitability, company size, or liquidity.